Interação da quitosana com surfactante e fenol em meio aquoso : cinética, equilíbrio e calorimetria - Mota, Jackeline Andrade (2012)
With the highly utilization of phenolic compounds and surfactant for several industrial sectors have been increasing the amount of unloading of these pollutant in the effluents, creating pollution. The sorption has getting attention for being an encouraging method for the removing of the chemical pollutants, found on the aqueous effluents. This thesis has the propose of evaluating the capacity of the sorption of the surfactant dodecyl benzene sodium sulfate (SDBS) in crosslinked chitosan beads with Epichlorohydrin (QUIT-EP) and the dichlorophenol-2,6-indophenol (DCFI) found in fish scales (Micropogonias furnieri) Changed with glutaraldehyde and chitosan. The chitosan spheres (QUIT-EP) present 67,8% of anionic surfactant remotion SDBS and the croaker fish scale (ESC-QUIT) removed 70,2% of the DCFI in the aqueous solution, proving the efficiency of these materials in the transference of the studied pollutants.